A thermally conductive rubber-plastic composite material and a preparation method thereof
By adding modified boron nitride and modified alumina to the rubber and plastic composite materials and using compatibilizers to improve matrix compatibility, the problem of difficult to take into account the thermal conductivity and mechanical properties of existing rubber and plastic materials is realized. Excellent thermal conductivity and good mechanical properties, and improve its flame retardant properties.
Patent Information
- Application Number
- CN202310857330.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-13
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2043-07-13
AI Technical Summary
While improving thermal conductivity, existing rubber and plastic materials are difficult to maintain good mechanical properties, and their flame retardant properties are insufficient, which limits their application in complex mechanical environments.
By adding modified boron nitride and modified alumina to the rubber-plastic composite materials, and using compatibilizers to improve matrix compatibility, building a dense thermal conductivity path, and introducing synergistic flame retardant components to improve the flame retardant performance of the material. .
It realizes excellent thermal conductivity and good mechanical properties of rubber and plastic composite materials, while at the same time imparting high-efficiency and safe flame retardant properties to the material, expanding its application range in complex application environments.
Smart Images

Figure QLYQS_1 
Figure BDA0004336384590000032 
Figure BDA0004336384590000041
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of rubber composite materials, and in particular, relates to a thermally conductive rubber-plastic composite material and a preparation method thereof. Background Art
[0002] Polypropylene materials have prominent disadvantages such as low-temperature brittleness, low impact strength, and large molding shrinkage. Therefore, it is necessary to toughen polypropylene materials. Toughened polypropylene materials are widely used in the field of engineering plastics and in industries such as automobiles, motorcycles, and home appliances. Yang Shenglin and others crushed fly ash to micron level and mixed it with EPDM rubber. The mixed rubber was melt-blended with polypropylene resin and injected into strips for testing. The results showed that adding mixed rubber can significantly improve the toughness of polypropylene materials, while the tensile strength did not decrease. However, the thermal conductivity is low and cannot meet the requirements of complex mechanical environment and high thermal conductivity at the same time, thus limiting the application of rubber and plastic products.
[0003] At present, the main method to improve the thermal conductivity of rubber and plastic materials is to fill them with inorganic fillers with high thermal conductivity. Generally, a high filler filling amount is required to form a thermal conduction path and improve thermal conductivity. At the same time, due to the poor compatibility between inorganic powder fillers and organic matrices, the addition of a large amount of inorganic powder fillers greatly reduces the mechanical properties of composite materials.
[0004] The Chinese invention patent with publication number CN104893307A discloses a thermally conductive insulating rubber-plastic composite material and its preparation method, wherein the thermally conductive filler is treated with a silane coupling agent, and then mixed with the rubber and plastic matrix, cold pressed, and vulcanized at high temperature. The application treats the surface of the thermally conductive filler with a silane coupling agent, which can improve the interface compatibility between the thermally conductive filler and the rubber and plastic matrix to a certain extent, but the silane coupling agent is generally an organic small molecule, so the modification effect is limited. Summary of the invention
[0005] The purpose of the present invention is to overcome the defects of the prior art and provide a thermal conductive rubber-plastic composite material and a preparation method thereof.
[0006] The rubber-plastic composite material of the present invention uses polypropylene and acrylic rubber as a matrix, and adds a compatibilizer, which can improve the compatibility of polypropylene and acrylic rubber and promote the formation of a rubber-plastic composite material with uniform texture; by adding modified boron nitride and modified aluminum oxide, the boron nitride can be evenly distributed in the material after modification, will not have a negative impact on the mechanical properties of the material, and can also overlap with the modified aluminum oxide to construct a denser and more complete heat conduction path, giving the material excellent thermal conductivity; in addition, a synergistic flame retardant component is also introduced into the surface of the modified boron nitride, which can give the rubber-plastic composite material efficient and safe flame retardant properties.
[0007] The purpose of the present invention can be achieved through the following technical solutions:
[0008] A thermal conductive rubber-plastic composite material, comprising the following raw materials, measured by weight: 50-60 parts of polypropylene, 30-40 parts of acrylic rubber, 10-14 parts of a compatibilizer, 16-20 parts of modified boron nitride, 15-18 parts of modified aluminum oxide, 3-4 parts of dicumyl peroxide, 3-5 parts of zinc oxide, 2-3 parts of stearic acid, and 0.8-1 part of an antioxidant;
[0009] The preparation method of the rubber composite material is specifically as follows:
[0010] Put polypropylene, acrylic rubber, compatibilizer, modified boron nitride, modified aluminum oxide, zinc oxide, stearic acid and antioxidant into an internal mixer and mix at 180-190°C, with a rotation speed of 800-1000r / min, mix for 20-25min, discharge the material, crush it, add dicumyl peroxide, put it into a twin-screw extruder for dynamic vulcanization, and discharge the material to obtain a rubber-plastic composite material.
[0011] Furthermore, the compatibilizer is one of polypropylene-maleic anhydride copolymer, polyethylene-maleic anhydride copolymer, and polyolefin elastomer-maleic anhydride graft copolymer.
[0012] Furthermore, the antioxidant is antioxidant 1010 or antioxidant 168.
[0013] Furthermore, the modified alumina is alumina treated with γ-glycidyloxypropyltrimethoxysilane.
[0014] Furthermore, the modified boron nitride is prepared by the following steps:
[0015] S1. Prepare hydroxylated nano boron nitride from dried hexagonal boron nitride by hydrothermal method; disperse hydroxylated nano boron nitride and KH550 in 95% ethanol aqueous solution by volume, ultrasonically treat for 30 min, stir and reflux at 60°C for 2 h, centrifuge, and repeatedly wash with anhydrous ethanol for 3-4 times, finally vacuum dry at 80°C for 12 h, grind to obtain pre-modified boron nitride; the dosage ratio of hydroxylated nano boron nitride, KH550 and ethanol aqueous solution is 10 g:22.1 g:100 mL;
[0016] The surface of hydroxylated boron nitride was treated by silane coupling agent KH550 (γ-aminopropyltriethoxysilane), and KH550 molecular chains were grafted on the surface of boron nitride. The structural formula is
[0017] S2. Place 2,4-diamino-1,3,5-triazine and dichloromethane in a three-necked flask, keep the temperature at 25-30°C, and stir to completely dissolve; mix 4-chloro-1-butene, sodium carbonate and THF (tetrahydrofuran), and then slowly drip into the three-necked flask using a constant pressure dropping funnel, stirring while adding, and continue to stir and react at 25-30°C for 3h after the addition is completed. After the reaction is completed, remove most of the solvent (dichloromethane and THF) by rotary evaporation, add distilled water and mix, then extract with dichloromethane, wash the organic phase with saturated NaCl aqueous solution for several times, and then with anhydrous Na 2 SO 4 Dry, filter, and finally remove dichloromethane by distillation under reduced pressure to obtain intermediate 1; the ratio of 2,4-diamino-1,3,5-triazine, 4-chloro-1-butene and sodium carbonate is 0.1 mol:0.21 mol:10.6 g;
[0018] Under the action of sodium carbonate, the -NH 2 A nucleophilic substitution reaction occurs with the -Cl on the 4-chloro-1-butene molecule. By controlling the molar ratio of the two to be close to 1:2, a chemical reaction as shown below occurs under the steric hindrance to obtain intermediate 1:
[0019]
[0020] S3, diethyl phosphite, CCl 4 and tetrahydrofuran were added to a three-necked flask with a stirring device in sequence, the flask was transferred to an ice bath and stirred, triethylamine and the dichloromethane solution of intermediate 1 were added dropwise to the flask at the same time, after the addition was completed, the three-necked flask was transferred to room temperature and stirred for 10 hours, after the reaction was completed, the filtrate was filtered, and the filtrate was rotary evaporated (to remove tetrahydrofuran, dichloromethane and CCl 4 ), to obtain a modifier; diethyl phosphite, CCl 4 , tetrahydrofuran, triethylamine, and intermediate 1 are used in a ratio of 13.8 g:15.4 g:30 mL:10.1 g:21.9 g; the concentration of the dichloromethane solution of intermediate 1 is 21.9 g / 50 mL;
[0021] The -NH- on the intermediate 1 molecule undergoes an Atherton-Todd reaction with dimethyl phosphite. By controlling the molar ratio of the two to be close to 1:1, the following reaction process occurs to obtain a modifier:
[0022]
[0023] S4, the intermediate 2, AIBN (azobisisobutyronitrile) and DMSO (dimethyl sulfoxide) were mixed and stirred in the ratio of 3.55 g:0.23 g:30 mL to obtain a reaction solution for later use; mercaptopropionic acid and DMSO were added to a four-necked flask with a stirring device, the temperature of the system was maintained at 70°C, and the reaction solution was added dropwise under stirring. After the addition was completed, the reaction was carried out at 70°C for 4 hours. After the reaction was completed, the mixture was washed with saturated brine and ethyl acetate, and the organic phase was taken and washed with anhydrous Na 2 SO 4 Dry, filter, and finally remove ethyl acetate by rotary evaporation to obtain a modifier; the ratio of mercaptopropionic acid, DMSO and reaction solution is 0.01 mol: 50 mL: 30 mL;
[0024] Under the action of AIBN, the unsaturated carbon-carbon double bond on the intermediate 2 undergoes a thiol-ene click reaction with the thiol group on the mercaptopropionic acid molecule. By controlling the molar ratio of the two to be close to 1:1, a chemical reaction process as shown below occurs to obtain a modifier;
[0025]
[0026] S5. Add the pretreated boron nitride and DMF (N,N-dimethylformamide) into a three-necked flask with a stirring device. After mechanically stirring at room temperature for 1 hour, add the modifier into the system and continue stirring for 30 minutes. Then add EDC-HCl (1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, coupling agent). Transfer the mixed solution to a 60°C water bath and continue stirring and reacting for 4 hours. After the reaction is completed, centrifuge and wash with DMF and ethanol aqueous solution (volume fraction 50%) for 4-5 times respectively. Finally, fully dry the product in a vacuum oven at 80°C and grind it to obtain modified boron nitride. The ratio of the amount of pretreated boron nitride, DMF, modifier and EDC-HCl is 10g:250mL:23.1g:0.8g.
[0027] The -COOH contained in the modifier molecule reacts with the -NH 2 An amidation reaction occurs to graft the modifier molecular chain onto the surface of boron nitride to obtain modified boron nitride. The process is as follows:
[0028]
[0029] Through the above series of reactions, an organic molecular chain is grafted on the surface of boron nitride through chemical bonding, and the organic molecular chain contains nitrogen heterocyclic rings, phosphate groups, unsaturated carbon-carbon double bonds and -NH- groups; on the one hand, an organic layer is formed on the surface of boron nitride through chemical modification, which can effectively improve the interfacial compatibility between inorganic boron nitride and polymer matrix, and promote the uniform dispersion of boron nitride; and the unsaturated carbon-carbon double bonds contained in the organic chain can participate in the mixing and vulcanization process of rubber and plastic materials, and react chemically with the polymer matrix (polypropylene and acrylic rubber), further improving the interaction force between boron nitride and the polymer matrix, thereby further improving the dispersion effect of boron nitride; uniform Boron nitride dispersed in rubber and plastic materials not only does not have a negative impact on the mechanical properties of the materials, but also can form a uniform lamellar heat conduction path, giving the materials good thermal conductivity; on the other hand, the -NH- on the organic molecular chain can react chemically with the epoxy groups on the surface of modified alumina to form lamellar and granular overlapping structures, so that boron nitride and alumina can work synergistically to build a denser and more complete thermal conduction path, further improving the thermal conductivity of rubber and plastic materials; it should be further explained that the nitrogen-containing rings and phosphate groups contained in the organic molecular chains belong to PN synergistic flame retardant components. As boron nitride is evenly distributed in the material, it gives the rubber and plastic materials safe and efficient flame retardant properties.
[0030] Beneficial effects of the present invention:
[0031] The rubber-plastic composite material of the present invention uses polypropylene and acrylic rubber as a matrix, and adds a compatibilizer, which can improve the compatibility of polypropylene and acrylic rubber, and promote the formation of a rubber-plastic composite material with uniform texture; by adding modified boron nitride and modified aluminum oxide, the boron nitride can be evenly distributed in the material after modification, and will not have a negative impact on the mechanical properties of the material, and can also overlap with the modified aluminum oxide to construct a more compact and perfect heat conduction path, giving the material excellent thermal conductivity; in addition, a synergistic flame retardant component is also introduced on the surface of the modified boron nitride, which can give the rubber-plastic composite material efficient and safe flame retardant properties. Finally, a thermally conductive rubber-plastic composite material with flame retardant properties and good mechanical properties is obtained, which has important application value. DETAILED DESCRIPTION
[0032] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0033] Example 1
[0034] Preparation of modified alumina:
[0035] Add 60 mL of γ-glycidyloxypropyltrimethoxysilane and 500 mL of ethanol aqueous solution (volume fraction of 50%) into a round-bottom flask, mix and dissolve evenly, then add 10 g of alumina. After ultrasonication for 10 min, reflux and stir at 82 ° C for 2 h, centrifuge and separate the product. Wash it with anhydrous ethanol for 4 times, and finally dry it in vacuum at 60 ° C and grind it to obtain modified alumina.
[0036] Example 2
[0037] Preparation of modified boron nitride:
[0038] S1. Prepare hydroxylated nano boron nitride from dried hexagonal boron nitride by hydrothermal method; disperse 10g hydroxylated nano boron nitride and 22.1g KH550 in 100mL 95% ethanol aqueous solution, ultrasonically treat for 30min, stir and reflux at 60℃ for 2h, centrifuge, wash repeatedly with anhydrous ethanol for 3 times, and finally vacuum dry at 80℃ for 12h, grind to obtain pre-modified boron nitride;
[0039] S2. Place 0.1 mol of 2,4-diamino-1,3,5-triazine and 100 mL of dichloromethane in a three-necked flask, keep the temperature at 25°C, and stir to completely dissolve; mix 0.21 mol of 4-chloro-1-butene, 10.6 g of sodium carbonate and 50 mL of THF, and then slowly drip into the three-necked flask using a constant pressure dropping funnel, stirring while adding, and continue to stir and react at 25°C for 3 hours after the addition is completed. After the reaction is completed, remove most of the solvent (dichloromethane and THF) by rotary evaporation, add distilled water to mix, and then extract with dichloromethane. Wash the organic phase with a saturated NaCl aqueous solution for several times and then with anhydrous Na 2 SO 4 Dry, filter, and finally remove dichloromethane by vacuum distillation to obtain intermediate 1;
[0040] S3, 13.8g of diethyl phosphite, 15.4g of CCl 4 and 30 mL of tetrahydrofuran were added to a three-necked flask with a stirring device in sequence, the flask was transferred to an ice bath and stirred, 10.1 g of triethylamine and 50 mL of a dichloromethane solution of the intermediate 1 (concentration of 21.9 g / 50 mL) were added dropwise to the flask at the same time, after the addition was completed, the three-necked flask was transferred to room temperature and stirred for 10 h, after the reaction was completed, the filtrate was filtered, and the filtrate was rotary evaporated (to remove tetrahydrofuran, dichloromethane and CCl 4 ), to obtain a modifier;
[0041] S4, 3.55g of intermediate 2, 0.23g of AIBN and 30mL of DMSO were mixed and stirred to obtain a reaction solution for standby use; 0.01mol of mercaptopropionic acid and 50mL of DMSO were added to a four-necked flask with a stirring device, the temperature of the system was maintained at 70°C, 30mL of the reaction solution was added dropwise under stirring, and the addition was completed. The reaction was carried out at 70°C for 4h. After the reaction was completed, the reaction was washed with saturated brine and ethyl acetate, and the organic phase was taken and washed with anhydrous Na 2 SO 4 Dry, filter, and finally remove ethyl acetate by rotary evaporation to obtain a modifier;
[0042] S5. Add 10 g of pretreated boron nitride and 250 mL of DMF into a three-necked flask with a stirring device. After mechanical stirring at room temperature for 1 hour, add 23.1 g of the modifier into the system and continue stirring for 30 minutes. Then add 0.8 g of EDC-HCl, transfer the mixture to a 60°C water bath and continue stirring and reacting for 4 hours. After the reaction is completed, centrifuge and wash with DMF and ethanol aqueous solution (50% by volume) for 4 times respectively. Finally, dry the product in a vacuum oven at 80°C and grind it to obtain modified boron nitride.
[0043] Example 3
[0044] Preparation of modified boron nitride:
[0045] S1. Prepare hydroxylated nano boron nitride from dried hexagonal boron nitride by hydrothermal method; disperse 20g hydroxylated nano boron nitride and 44.2g KH550 in 200mL 95% ethanol aqueous solution, ultrasonically treat for 30min, stir and reflux at 60℃ for 2h, centrifuge, wash repeatedly with anhydrous ethanol for 4 times, and finally vacuum dry at 80℃ for 12h, grind to obtain pre-modified boron nitride;
[0046] S2. 0.2 mol of 2,4-diamino-1,3,5-triazine and 200 mL of dichloromethane were placed in a three-necked flask, the temperature was maintained at 30°C, and the mixture was stirred to completely dissolve; 0.42 mol of 4-chloro-1-butene, 21.2 g of sodium carbonate and 100 mL of THF were mixed and then slowly dripped into the three-necked flask using a constant pressure dropping funnel, and stirred while adding. After the addition was completed, the reaction was continued at 30°C with stirring for 3 hours. After the reaction was completed, most of the solvent (dichloromethane and THF) was removed by rotary evaporation, distilled water was added and mixed, and then extracted with dichloromethane. The organic phase was washed several times with a saturated aqueous solution of NaCl and then with anhydrous Na 2 SO 4 Dry, filter, and finally remove dichloromethane by vacuum distillation to obtain intermediate 1;
[0047] S3, 27.6g of diethyl phosphite, 30.8g of CCl 4 and 60 mL of tetrahydrofuran were added to a three-necked flask with a stirring device in sequence, the flask was transferred to an ice bath and stirred, 20.2 g of triethylamine and 100 mL of a dichloromethane solution of the intermediate 1 (concentration of 21.9 g / 50 mL) were added dropwise into the flask at the same time, after the addition was completed, the three-necked flask was transferred to room temperature and stirred for 10 h, after the reaction was completed, the filtrate was filtered, and the filtrate was rotary evaporated (to remove tetrahydrofuran, dichloromethane and CCl 4 ), to obtain a modifier;
[0048] S4, 7.1g of intermediate 2, 0.46g of AIBN and 60mL of DMSO were mixed and stirred to obtain a reaction solution for standby use; 0.02mol of mercaptopropionic acid and 100mL of DMSO were added to a four-necked flask with a stirring device, the temperature of the system was maintained at 70°C, 60mL of the reaction solution was added dropwise under stirring, and the addition was completed. The reaction was carried out at 70°C for 4h. After the reaction was completed, the reaction was washed with saturated brine and ethyl acetate, and the organic phase was taken and washed with anhydrous Na 2 SO 4 Dry, filter, and finally remove ethyl acetate by rotary evaporation to obtain a modifier;
[0049] S5. Add 20 g of pretreated boron nitride and 500 mL of DMF into a three-necked flask with a stirring device. After mechanical stirring at room temperature for 1 hour, add 46.2 g of the modifier into the system and continue stirring for 30 minutes. Then add 1.6 g of EDC-HCl, transfer the mixture to a 60°C water bath and continue stirring and reacting for 4 hours. After the reaction is completed, centrifuge and wash with DMF and ethanol aqueous solution (50% by volume) for 5 times respectively. Finally, dry the product in a vacuum oven at 80°C and grind it to obtain modified boron nitride.
[0050] Example 4
[0051] Preparation of rubber composites:
[0052] According to weight proportions, 50 parts of polypropylene, 30 parts of acrylic rubber, 10 parts of polypropylene-maleic anhydride copolymer, 16 parts of modified boron nitride obtained in Example 2, 15 parts of modified alumina obtained in Example 1, 3 parts of zinc oxide, 2 parts of stearic acid and 0.8 parts of antioxidant 1010 were put into an internal mixer and mixed at 180° C., with a rotation speed of 800 r / min. The mixture was mixed for 20 min, discharged, crushed, and 3 parts of diisopropylbenzene peroxide were added. The mixture was put into a twin-screw extruder for dynamic vulcanization and discharged to obtain a rubber-plastic composite material.
[0053] Example 5
[0054] According to weight proportions, 55 parts of polypropylene, 35 parts of acrylic rubber, 12 parts of polyethylene-maleic anhydride copolymer, 18 parts of modified boron nitride obtained in Example 3, 16.5 parts of modified alumina obtained in Example 1, 4 parts of zinc oxide, 2.5 parts of stearic acid and 0.9 parts of antioxidant 168 were put into an internal mixer and mixed at 185°C, with a rotation speed of 900 r / min for 23 min. The material was discharged and crushed, and 3.5 parts of diisopropylbenzene peroxide were added. The material was put into a twin-screw extruder for dynamic vulcanization and discharged to obtain a rubber-plastic composite material.
[0055] Example 6
[0056] According to weight proportions, 60 parts of polypropylene, 40 parts of acrylic rubber, 14 parts of polyolefin elastomer-maleic anhydride graft copolymer, 20 parts of modified boron nitride prepared in Example 2, 18 parts of modified alumina prepared in Example 1, 5 parts of zinc oxide, 3 parts of stearic acid and 1 part of antioxidant 1010 were put into an internal mixer and mixed at 190°C, with a rotation speed of 1000 r / min. The mixture was mixed for 25 minutes, discharged, crushed, and 4 parts of diisopropylbenzene peroxide were added. The mixture was put into a twin-screw extruder for dynamic vulcanization and discharged to obtain a rubber-plastic composite material.
[0057] Comparative Example
[0058] The modified boron nitride in Example 4 is replaced by ordinary boron nitride, and the other raw materials and preparation process remain unchanged to obtain a rubber-plastic composite material.
[0059] The rubber-plastic composite materials obtained in Examples 4-6 and the comparative example were processed and cut into test samples, and the following performance tests were performed:
[0060] Test the tensile properties of rubber materials according to GB / T528-1998;
[0061] Flame retardant grade tested according to UL94-V0 standard:
[0062] The thermal conductivity of the material was tested using a flash thermal conductivity meter;
[0063] The measured results are shown in the following table:
[0064]
[0065]
[0066] It can be seen from the data in the above table that the rubber-plastic composite material obtained by the present invention has good mechanical properties and flame retardant properties, and excellent thermal conductivity; combined with the data of the comparative example, it can be seen that after the modification, boron nitride can not only be evenly distributed in the material, without negatively affecting the mechanical properties of the material, but also can give the material good flame retardant properties, and synergize with modified alumina to greatly improve the thermal conductivity of the material.
[0067] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0068] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.
Claims
1. A thermally conductive rubber-plastic composite material, characterized in that: The raw materials include the following in parts by weight: 50-60 parts of polypropylene, 30-40 parts of acrylic rubber, 10-14 parts of compatibilizer, 16-20 parts of modified boron nitride, 15-18 parts of modified aluminum oxide, 3-4 parts of dicumyl peroxide, 3-5 parts of zinc oxide, 2-3 parts of stearic acid, and 0.8-1 parts of antioxidant; Wherein, the modified alumina is alumina treated with γ-glycidyloxypropyltrimethoxysilane; The modified boron nitride is prepared by the following steps: S1, preparing hydroxylated nano boron nitride by a hydrothermal method, and then treating it with KH550 to obtain pre-modified boron nitride; S2, 2,4-diamino-1,3,5-triazine and dichloromethane are placed in a three-necked flask, the temperature is maintained at 25-30°C, and stirred to completely dissolve; 4-chloro-1-butene, sodium carbonate and THF are mixed and then slowly dripped into the three-necked flask using a constant pressure dropping funnel, stirring while adding, and after the addition is completed, stirring and reacting at 25-30°C for 3 hours. After the reaction is completed, post-treatment is performed to obtain intermediate 1; S3, diethyl phosphite, CCl4 and tetrahydrofuran are added to a three-necked flask with a stirring device in sequence, the flask is transferred to an ice bath and stirred, triethylamine and a dichloromethane solution of the intermediate 1 are added dropwise to the flask at the same time, after the addition is completed, the three-necked flask is transferred to room temperature and stirred for reaction for 10 hours, after the reaction is completed, the filtrate is filtered, and the filtrate is evaporated to obtain the intermediate 2; S4, the intermediate 2, AIBN and DMSO were mixed and stirred in the ratio of 3.55g:0.23g:30mL to obtain a reaction solution for standby use; mercaptopropionic acid and DMSO were added to a four-necked flask with a stirring device, the temperature of the system was maintained at 70°C, and the reaction solution was added dropwise under stirring. After the addition was completed, the reaction was carried out at 70°C for 4h. After the reaction was completed, the mixture was washed with saturated brine and ethyl acetate system, the organic phase was taken, dried with anhydrous Na2SO4, filtered, and finally ethyl acetate was removed by rotary evaporation to obtain a modifier; S5. Add the pretreated boron nitride and DMF into a three-necked flask with a stirring device. After mechanical stirring at room temperature for 1 hour, add the modifier into the system and continue stirring for 30 minutes. Then add EDC-HCl, transfer the mixed solution to a 60°C water bath and continue stirring and reacting for 4 hours. After the reaction is completed, centrifuge and wash with DMF and ethanol aqueous solution for 4-5 times respectively. Finally, fully dry the product in a vacuum oven at 80°C and grind it to obtain modified boron nitride. The structural formula is shown below: 。 2. The thermally conductive rubber-plastic composite material according to claim 1, characterized in that: The specific operation of step S1 is as follows: preparing hydroxylated nano boron nitride by a hydrothermal method from dried hexagonal boron nitride; dispersing hydroxylated nano boron nitride and KH550 in an ethanol aqueous solution with a volume fraction of 95%, ultrasonically treating for 30 minutes, stirring and refluxing at 60°C for 2 hours, centrifuging, and repeatedly washing with anhydrous ethanol for 3-4 times, and finally vacuum drying at 80°C for 12 hours, grinding, and obtaining pre-modified boron nitride; the dosage ratio of hydroxylated nano boron nitride, KH550 and ethanol aqueous solution is 10g:22.1g:100mL.
3. The thermally conductive rubber-plastic composite material according to claim 1, characterized in that: In step S2, the ratio of 2,4-diamino-1,3,5-triazine, 4-chloro-1-butene and sodium carbonate used is 0.1 mol:0.21 mol:10.6 g.
4. The thermally conductive rubber-plastic composite material according to claim 1, characterized in that: In step S3, the ratio of diethyl phosphite, CCl4, tetrahydrofuran, triethylamine and intermediate 1 is 13.8 g:15.4 g:30 mL:10.1 g:21.9 g; the concentration of the dichloromethane solution of intermediate 1 is 21.9 g / 50 mL.
5. The thermally conductive rubber-plastic composite material according to claim 1, characterized in that: In step S4, the ratio of mercaptopropionic acid, DMSO and reaction solution is 0.01 mol:50 mL:30 mL.
6. The thermally conductive rubber-plastic composite material according to claim 1, characterized in that: In step S5, the ratio of the amount of pretreated boron nitride, DMF, modifier and EDC-HCl is 10 g: 250 mL: 23.1 g: 0.8 g.
7. The thermally conductive rubber-plastic composite material according to claim 1, characterized in that: The compatibilizer is one of polypropylene-maleic anhydride copolymer, polyethylene-maleic anhydride copolymer, and polyolefin elastomer-maleic anhydride graft copolymer.
8. The method for preparing a thermally conductive rubber-plastic composite material according to claim 1, characterized in that: The steps include: Put polypropylene, acrylic rubber, compatibilizer, modified boron nitride, modified aluminum oxide, zinc oxide, stearic acid and antioxidant into an internal mixer and mix at 180-190°C, discharge the material, crush it, add dicumyl peroxide, put it into a twin-screw extruder for dynamic vulcanization, discharge the material, and obtain a rubber-plastic composite material.
Citation Information
Patent Citations
Heat-conduction electric-insulation rubber-plastic composite material and preparation method thereof
CN104893307A
Preparation method and product of heat-conductive thermoplastic vulcanized rubber elastomer material
CN109021408A
Heterostructure heat-conducting filler, preparation method and application thereof, silicone rubber heat-conducting insulating composite material and preparation method of same
CN113087971A
Flame-retardant polypropylene plastic
CN116253951A